Optimization of a flood diversion gate scheme in flood storage and detention areas based on flood numerical simulation - Yu, Ping; Ma, Huixin; Qiu, Lanqing; Zhang, Ting; Li, Shaofei (Frontiers in Environmental Science, 2022)
Flood storage and detention area is an important part of the river flood control system and an effective measure to ensure flood control safety and mitigate disasters in key areas. Taking the flood storage and detention area of DaHuangPuWa as an example, the flood diversion process of different positions on Jinbao highway was simulated numerically. The water level, velocity, and flow rate of each observation point during the 100-year flood were calculated respectively. After comprehensive analysis, it is determined that the location of the diversion gate in the flood storage and detention area is better at the diversion gate of liuwanzhuang. The results of this paper show that the numerical simulation method can provide more scientific and reasonable theoretical support for the design of flood diversion gates in flood storage and detention area.